From bilateral arbitral tribunals and investment courts to a multilateral investment court : options regarding the institutionalization of investor-state dispute settlement /: options regarding the institutionalization of investor-state dispute settlement. (2020) - Bungenberg, Marc; Reinisch, August
No abstract available